Educational Game Design for Introduction to Traditional Indonesian Houses Based on Leap Motion for Elementary School Students - Anggraini, Cicilia Clara Devi; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Dewi, Danar Kristiana; Fadloli, Fadloli (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Design of a Leap Motion-Based Educational Game on the Introduction of Indonesian Traditional Houses for Elementary School Students. This research aims to design a Leap Motion-based educational game as an innovative learning media in introducing Indonesian traditional houses to elementary school students. The background is based on the limited interactive learning media used in cultural education, especially on the material of traditional houses which have been taught with conventional approaches. Using Research and Development (R&D) approach with the ADDIE development model, the research focused on the needs analysis stage through interviews and distributing questionnaires to education experts, elementary school teachers, and students. The results of the analysis showed that learning about traditional houses is still static and uninteresting, so it is unable to build a contextualized learning experience. Both teachers and students showed high enthusiasm for the use of gesture-based media that allows visual and kinesthetic interaction. Leap Motion is considered to have high potential in realizing embodied learning that can increase student engagement and understanding. Experts recommended 3D visualization features, gesture-based navigation and cultural narrative in the game. These findings provide a conceptual and empirical foundation for the development of the ArchiLeap: Jelajah Rumah Adat Nusantara that bridges the richness of local culture with an adaptive, fun, and contextualized digital technology approach.